Religious Riots and Electoral Politics in India - Sriya Iyer; Anand Shrivastava (Institute for the Study of Labor (IZA), 2015)
The effect of ethnic violence on electoral results provides useful insights into voter behaviour in democratic societies. Religious riots have claimed more than 14,000 lives in India since 1950. We study the effect of Hindu-Muslim riots on election results in India. We combine data on riots, which have been geo-coded, with electoral data on state legislature elections and control variables on demographics and public goods provision to construct a unique panel data set for 16 large states in India over a 21 year period from 1981-2001. We suggest a new instrument that draws upon the random variation in the day of the week that important Hindu festivals fall on in each year, as set by a lunar calendar. The probability of a riot increases if a Hindu festival falls on a Friday, the holy day for Muslims. This allows us to isolate the causal effect of riots on electoral results. We also correct for under-reporting of riots and how they affect electoral outcomes in nearby districts. We find that riots occurring in the year preceding an election increases the vote share of the Bharatiya Janata Party by 5 to 7 percentage points in the election.
Keywords: Z12; D72; D74; 330; religion; elections; riots; India